2022
DOI: 10.1002/chem.202103710
|View full text |Cite
|
Sign up to set email alerts
|

Laser Desorption/Ionization Mass Spectrometry Imaging: A New Tool to See through Nanoscale Particles in Biological Systems

Abstract: Understanding the fate of nanoscale particles (NPs) in biological systems is significant with the increasing risk for human exposure. Recent research endeavors in laser desorption/ionization mass spectrometry imaging (LDI‐MSI) have enriched the toolbox for evaluation of NPs’ behavior in biological tissues, especially in aspects including sub‐organ bio‐distribution, clearance, quantification and surface chemistry variation analysis. In recognition of the potential for advancement in LDI MSI, this concept provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Currently, methods for the detection of exogenous materials in tissue have been developed including fluorescence imaging, positron emission tomography, magnetic resonance imaging, , and transmission electron microscopy. However, these techniques lack the depth and coverage of molecular information in situ. Accordingly, it is essential to develop a method for simultaneous mapping of the distribution of NPs and their spatial metabolic effects, as this information is critical to understanding the mechanisms of nanomaterials-aided diagnosis and therapy. Mass spectrometry imaging (MSI) allows the visualization and quantitation of elements and molecules in complex biological systems with distinct features including high throughput, label-free, high sensitivity, and high spatial resolution. MSI has become an indispensable tool for spatial metabolomics, which has broken through the limitation of obtaining the depth and coverage of molecular information in tissue. , While the application of mass spectrometry imaging is still limited by resolution, through technological advances, the resolution has been able to exceed that of suborgans and reach the level of a single cell .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, methods for the detection of exogenous materials in tissue have been developed including fluorescence imaging, positron emission tomography, magnetic resonance imaging, , and transmission electron microscopy. However, these techniques lack the depth and coverage of molecular information in situ. Accordingly, it is essential to develop a method for simultaneous mapping of the distribution of NPs and their spatial metabolic effects, as this information is critical to understanding the mechanisms of nanomaterials-aided diagnosis and therapy. Mass spectrometry imaging (MSI) allows the visualization and quantitation of elements and molecules in complex biological systems with distinct features including high throughput, label-free, high sensitivity, and high spatial resolution. MSI has become an indispensable tool for spatial metabolomics, which has broken through the limitation of obtaining the depth and coverage of molecular information in tissue. , While the application of mass spectrometry imaging is still limited by resolution, through technological advances, the resolution has been able to exceed that of suborgans and reach the level of a single cell .…”
Section: Introductionmentioning
confidence: 99%
“…16−18 However, these techniques lack the depth and coverage of molecular information in situ. Accordingly, it is essential to develop a method for simultaneous mapping of the distribution of NPs and their spatial metabolic effects, 19 as this information is critical to understanding the mechanisms of nanomaterials-aided diagnosis and therapy. Mass spectrometry imaging (MSI) allows the visualization and quantitation of elements and molecules in complex biological systems with distinct features including high throughput, label-free, high sensitivity, and high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we used a subatmospheric pressure (subAP) dual MALDI/ESI source interfaced to an orbital trap for imaging of Au NPs; signals were detected from as low as ten 50 nm AuNPs . Furthermore, the technique has a great potential for multiplexed SP detection of NPs with different elemental compositions and simultaneous detection of various ligands attached to the NP surface …”
Section: Introductionmentioning
confidence: 99%
“…25 Furthermore, the technique has a great potential for multiplexed SP detection of NPs with different elemental compositions and simultaneous detection of various ligands attached to the NP surface. 26 Here we report the LDI MSI method for single-NP detection employing specific gas-phase reactions in a subAP ion source connected to an orbital trapping MS. Special attention is paid to sample preparation to achieve deposition of separated individual NPs over a predefined area. The data processing is essential, showing potential difficulties and uncertainty of evaluation, which leads to different numbers of detected NPs in the prepared samples.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Laser desorption/ionization mass spectrometry (LDI-MS) is a powerful mass spectrometry tool with attractive properties such as high throughput, simple and minimal sample preparation, and rapid analysis. [26][27][28] Meanwhile, LDI is a relatively so ionization technique that can retain certain cluster structures when ionizing particulate materials. 4,29,30 Herein, by using PFASs as a typical set of OC and carbon black (CB) as a standard and alternative soot material (i.e., a model EC), we found that LDI-MS generated two kinds of independent and specic characteristic MS ngerprint peaks for EC and OC.…”
Section: Introductionmentioning
confidence: 99%